Stroke in women: epidemiology, risk and prevention - Bushnell, Cheryl (Henry Stewart Talks, 2018)
Epidemiology of sex differences, Stroke Prevention in Women Guideline, Stroke risk factors unique to, or more prevalent in, women than men, Pregnancy complications, Menopause, Hormonal contraception and replacement, Atrial fibrillation, Risk screening and prevention, including primary prevention, Summary and future directions